New urbanism principles intervention with CPTED concept in open, guarded neighborhoods and gated community - Abdulaziz Merghani, Adbulaziz Salah (2022)
with emergence of new urbanism concept in 1970s, the planning pattern has changed dramatically which support the principles has been proposed by congress of new urbanism. Crime rate in developing neighbourhoods has significantly increase which make residents under danger of robbery. The aim of thesis is to examine new urbanism principles incorporated with CPTED concept toward open, guarded neighbourhood and gated community in Johor Bahru, Malaysia. The three objectives under identifying new urbanism characteristics incorporated with crime prevention through environmental design. Second objective, examine new urbanism principles and CPTED concept. Third objective, proposing conceptual comparison between open, guarded neighbourhood and gated community in term of new urbanism principles and CPTED concept in Johor Bahru. However, the research has contribution on neighbourhood development in term of walkability, connectivity, mixed-use building and quality of architecture which enlighten urban developers and planners toward neighbourhood development. Thus, observation method and google map data were used in this study to gain accurate information gathering while the usage of analysis was underpinned on AHP analysis, sensitive analysis, frequency analysis and connectivity street analysis graph. Afterwards, the various results were shown in three neighbourhoods in term of walkability, connectivity, mixed-use building and quality of architecture interact with CPTED concept that Taman University appear positive result of walking mode and mixed-use building but negative result in term of connectivity and quality of architecture in safety and quality. Moreover, Opal Mutiara Mas showed strong result in term of safety that related to walkability and quality of architecture but lack of mixed-use building principles. Furthermore, the seed Sutera highlight impressive result in term of connectivity, quality of architecture and walkability in term of safety and quality but missing of mixed-use building in term of public amenities which was obvious from the comparison between three neighbourhoods. The comparison between open, guarded and gated neighbourhood will open eyes on applying CPTED concept and new urbanism theory in development process that can contribute in integration planning